Pengaruh Model Pembelajaran Think Talk Write (TTW) Terhadap Kemampuan Menggali Informasi Teks Narasi Siswa Kelas V SD - Sistiara, Elma; Wardiah, Desyy; Kuswidyanarko, Arief (Institut Teknologi Pendidikan Indonesia, 2022)
The problem in this study is that the value of Indonesian subjects is still low, especially in the ability to explore narrative text information for fifth-grade students and students pay less attention when the teacher explains learning. The population in this study were fifth-gradestudents of SD Negeri 23 Palembang. This research uses quantitative methods, and this type of research is a Two-Groub Pretest-Posttest Control Group Design, Pretest-Posttest Experimental Group Design. Data collection techniques in this study are tests, observations, and documentation. The average pretest result for the control class ranges from 47 with inaccurate criteria, the average pretest result for the experimental class ranges in value 63 with the correct criteria, the average posttest result for the control class is 67 with the right criteria, and the average posttest result for the experimental class is 80 with very precise criteria and hypothesis testing using Paired sample t-test which shows that the 2-tailed sig value is 0.000 <0.05. This proves that the Think Talk Write (TTW) learning model can affect the ability to explore narrative text information for fifth-grade students. Therefore, the Think Talk Write (TTW) learning model can be a solution to improving students' ability to explore narrative text information in their eyes. Indonesian lessons.